Evaluation of Serum Testosterone, Progesterone, Seminal Antisperm Antibody, and Fructose Levels among Jordanian Males with a History of Infertility - Hala I. Al-Daghistani; Abdul-Wahab R. Hamad; Muna Abdel-Dayem; Mohammad Al-Swaifi; Mohammad Abu Zaid (Biochemistry Research International)
Due to the biochemical complexity of seminal fluid, we attempt to study the possible correlation between fructose, which is secreted under the effect of androgen hormone, and autoimmunity, which might play a role in varicocele associated infertility, in reducing sperm motility. Seminal fructose, antisperm antibodies (ASAs) and blood steroids hormones (testosterone and progesterone) levels were measured in 66 infertile males with varicocele and 84 without varicocele referred for fertility treatment. Seminal analysis was performed with biochemical measurements of seminal fructose and mixed agglutination reaction (MAR) for ASA. Serum levels of progesterone and testosterone were estimated using a competitive chemoluminescent enzyme immunoassay. The mean values for serum testosterone were 380.74±24.331, 365.9±16.55, and 367.5±21.8 ng/dl, progesterone 0.325±0.243, 0.341±0.022, and 0.357  ±  0.0306 ng/ml, and seminal plasma fructose 359.6  ±  26.75, 315.6  ±  13.08, and 332.08  ±  24.38 mg/dl in males with varicocele, without varicocele, and fertile males, respectively. A significant high level of testosterone was observed within varicocele group (P=.001). This result showed that testosterone may play a role as an infertility determinant in subjects with varicocele. ASA was detected in 18 (26.47%) of cases with varicocele, 20 (38.46%) without varicocele, and in 16 (32.0%) fertile men. Cases with ASAs associated with low sperm motility morphology. An inverse correlation between sperm-bound antibodies and viscosity has been shown (P=.017). ASA showed some significant inverse relations with ages, durations of infertility, and viscosity (P<.05). In addition, a significant correlation was observed between ASA positive seminal plasma and testosterone concentration among infertile cases (with or without varicocele) and fertile (P<.05). Our results suggest a relationship between testicular steroid hormone levels with autoimmunity and sperm antibodies which influence the motility of ejaculated spermatozoa among Jordanian infertile males.